Strategi Kewirausahaan dan Faktor Penentu Pertumbuhan Usaha Busana Muslim: Studi pada Desa Sungai Pinang, Kecamatan Rambutan, Kabupaten Banyuasin - Muhammad Nur Ismail; Ulil Amri (CV. Era Digital Nusantara, 2025)
The background of this research is that business development is a very important thing that must be done by entrepreneurs, because an entrepreneur is said to be successful if he is able to develop the business he manages. By knowing the factors that influence business development, the business can be developed in a better direction. This research aims to find out what factors encourage and inhibit the development of Muslim fashion businesses in Sungai Pinang Village, Rambutan District, Banyuasin Regency, to find out what entrepreneurs' strategies are in dealing with business obstacles. This research aims to find out how entrepreneurial strategies are in dealing with factors that influence the development of Muslim fashion businesses. This research uses qualitative methods. Data collection was carried out using interviews and documentation methods. The data that has been collected is then analyzed using a descriptive approach, namely the approach used to analyze data by describing the data that has been collected as it is. The results of the research show that Entrepreneurial Strategies in Facing Barriers to Muslim Fashion Business in Sungai Pinang Village. Every business experiences obstacles, but there are always solutions to minimize them. Entrepreneurs need to have strategies to minimize failure and understand the factors that support business success. The strategies of entrepreneurs in Sungai Pinang Village to develop a Muslim fashion business include: Managing Financial Resources by developing a financial information system for making business decisions. Entrepreneurs need to understand the health of their business to be able to control it. Managing employees effectively is very important because business owners cannot work alone.